Poor Metabolic Health Increases COVID-19-Related Mortality in the UK Biobank Sample - Morys, Filip; Dagher, Alain (Frontiers in Endocrinology, 2021)
Previous studies link obesity and components of metabolic health, such as hypertension or inflammation, to increased hospitalisations and mortality of patients with COVID-19. Here, in two overlapping samples of over 1,000 individuals from the UK Biobank we investigate whether metabolic health as measured by waist circumference, dyslipidaemia, hypertension, type 2 diabetes, and systemic inflammation is related to increased COVID-19 infection and mortality rate. Using logistic regression and controlling for confounding variables such as socioeconomic status, age, sex or ethnicity, we find that individuals with worse metabolic health (measured on average eleven years prior to 2020) have an increased risk for COVID-19-related death (adjusted odds ratio: 1.67). We also find that specific factors contributing to increased mortality are increased serum glucose levels, systolic blood pressure and waist circumference.